Avaliação da eficácia e efetividade do Programa de Erradicação do Trabalho Infantil a partir da perspectiva dos usuários e agentes - Gouveia, Charlene Nayana Nunes Alves (2013)
The Evaluation one of the steps of a public policy that identifies inefficient and ineffective actions and, therefore, plan, design and implements alternative actions involving desired outcomes and impacts. The Child Labor Eradication Program (PETI) was born in 1996 with the aim to remove children 7-15 years of the study, or prevent such a situation, and put them in school. The argument is that the PETI is a public policy that provides effective, exerting positive impact in the lives of your target audience, and effective in preventing early labor and situations of vulnerability, however is ineffective when it comes to labor eradication child. The overall objective is to evaluate the efficacy and effectiveness of PETI in Paraiba State , from the perspective of users (children, adolescents and families) and agents involved in the program (social agents, facilitators of workshops and technical reference). We also intend to develop a valid and reliable survey instrument for this purpose. To meet the objectives of this thesis, three studies conducted up. Overall, 1,012 participants were selected from several municipalities in Paraíba. In the Study I, we interviewed 20 children and teenagers using the program, representatives of 20 families and 8 agents. The responses were subjected to content analysis of Bardin. From the dimensions found were elaborate theoretical models and items in each instrument. After an analysis of judges and a semantic validation, the necessary adjustments were made and the instruments began to construct validation. In the Study II participated in 395 children and adolescents, 201 families and 118 agents. The construct validity of the instruments was verified by a Common Factor Analysis (CFA) using the Principal Component (PC) technique, with varimax rotation. The best solution to the students confirmed the theoretical model with four dimensions, however the theoretical model of the families was not corroborated, having adopted the solution with five statistical dimensions. The agents not showed statistically satisfactory solution, and remained the theoretical model. The precision of the measurements was checked by Cronbach's alpha, yielding satisfactory rates for students (0.831) and families (0.775), but not for the agents (0.561). From these analyzes, the items were chosen and adjusted, and went to the next study in order to carry out their final testing. Study III, attended by 80 children or adolescents, 45 families and 27 agents. Average ratios were generated for each of the factors of the instruments. Considering the scale of responses from 6 points in all factors - Involvement with the Work, Work to Combat Early Impacts of PETI, Evaluation, Satisfaction with Working Conditions, Overall PETI - participants scored between indices satisfying (3.6) and high (6). The thesis proposal was confirmed, and it was concluded that the PETI is effective in preventing early labor and in situations of vulnerability, but does not eradicate these situations. In addition, it presents indicators of effectiveness, causing positive changes in the lives of users.